Pengaruh CSR Disclosure, Kebijakan Dividen, dan Risiko Keuangan Terhadap Kinerja Keuangan yang Dimoderasi Struktur Modal - Yarika Azhara; Nera Marinda Machdar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In era of globalization, there are many industries can improve the economic welfare of the Indonesian people. If Indonesian companies want to improve people's welfare, they must perform better to achieve maximum profits. The researcher created this scientific article, aiming to study and examine the influence of CSR disclosure, dividend policy and financial risk on financial performance which is moderated by capital structure. This research uses a qualitative descriptive method for literature study. The results of this research indicate that the variables corporate social responsibility disclosure, dividend policy, and financial risk have an influence on financial performance. As well as corporate social responsibility disclosure, dividend policy and financial risk can be moderated by capital structure on financial performance.